Caught In the Act::Danish Post-Imperial Anxieties Trapped between Colonial Erasure and Restaging - Jensen, Lars (2013)
How do we understand the flows of people in the form that globalisation currently has – within Europe? This is, it seems to me, the question that informs the title of the symposium. My paper seeks to locate this question in a Danish context. This, I shall argue, requires establishing a reading of the Danish colonial archive (following Stoler) and a way of ‘grounding’ (Hall) a blend of postcolonial, decolonial, whiteness and critical race theories in a Danish context. Denmark has not only not acknowledged its history as a colonial power, and more generally its participation in ‘colonial adventures’, it has through its nation-building process after the second world war sought to erase its imperial history. This strategy has been enabled internationally through a self-staging as an (altruistic) major development aid contributor and international and domestic (benevolent) overseer of the modernisation process in Greenland. Domestically, the welfare society has been cast as the guarantor of the (immaculate) imagined community (Anderson), whose gradual erosion since the 1970s requires a new narrative that leaves intact the immaculate imagined community, and hence looks for threats/destroyers/culprits outside the imagined community. I shall furthermore argue that while the acuteness of the current financial crisis invites explanations that look to social exclusions as a result of acute austerity, there is little, in fact, in the Danish context which suggests this explanation holds in terms of cultural processes of ostracisation. What I am going to discuss then is how we may understand the relationship between how the long term processes of cultural exclusion relate to more acutely produced social crises, and how again this may be linked to the colonial archive and its national particularities.